Atividades desenvolvidas pelo Serviço de Inspeção Federal (SIF) em matadouro frigorífico de Araguaína. - Barros, Lwangia Silveira (Universidade Federal do Tocantins, 2023)
The supervised curricular internship was held from March 20 to June 2, 2017, at the Federal Inspection Service (SIF) under nº 723 at LKJ Frigorific Ltda in the city of Araguaína in the state of Tocantins. The area chosen was the inspection and meat technology, under the guidance of Professor Maria de Oliveira Lobo and supervision of the Federal Agricultural Audit Dr. Dagoberto Machado Prata, totaling 378 hours of internship. During this period the objective was to follow the steps of pre-slaughter, slaughtering and processing of the meat and the actions of the inspection service, and to collect data on the main causes of partial and / or total condemnation of carcasses. The accomplishment of the internship in this area allowed to increase the knowledge of meat inspection, to experience the activities of the veterinarian in the service of sanitary inspection, consolidating the learning acquired in the graduation and preparing itself better for the labor market. The period of internship in the slaughterhouse reinforces the importance of the veterinarian in the implementation of good breeding practices and in the sanitary inspection of meat in order to identify diseases that may directly affect the food safety of consumers and negatively influence the meat trade in geral.